The bricks that built the houses - Tempest, Kae, 1985- (Bloomsbury, 2017)
It gets into your bones. You don't even realise it, until you're driving through it, watching all the things you've always known and leaving them behind. Young Londoners Becky, Harry and Leon are escaping the city in a fourth-hand Ford Cortina with a suitcase full of stolen money. Taking us back in time - and into the heart of London - The Bricks that Built the Houses explores a cross-section of contemporary urban life with a powerful moral microscope, giving us intimate stories of hidden lives, and showing us that good intentions don't always lead to the right decisions. Leading us into the homes and hearts of ordinary people, their families and their communities, Kate Tempest exposes moments of beauty, disappointment, ambition and failure. Wise but never cynical, driven by empathy and ethics, The Bricks the Built the Houses questions how we live with and love one another.